PHiD-CV induces anti-Protein D antibodies but does not augment pulmonary clearance of nontypeable Haemophilus influenzae in mice. Issue 38 (11th September 2015) - Siggins, Matthew K.; Gill, Simren K.; Langford, Paul R.; Li, Yanwen; Ladhani, Shamez N.; Tregoning, John S.
Abstract: Background: A recently-licensed 10-valent pneumococcal conjugate vaccine (PHiD-CV; Synflorix, GSK) uses Protein D from Haemophilus influenzae as a carrier protein. PHiD-CV therefore has the potential to provide additional protection against nontypeable H. influenzae (NTHi). NTHi frequently causes respiratory tract infections and is associated with significant morbidity and mortality worldwide and there is currently no vaccine. Methods: We developed mouse models of NTHi infection and influenza/NTHi superinfection. Mice were immunized with PHiD-CV, heat-killed NTHi, or a 13-valent pneumococcal conjugate vaccine that did not contain Protein D (PCV13; Prevenar, Pfizer) and then infected intranasally with NTHi. Results: Infection with NTHi resulted in weight loss, inflammation and airway neutrophilia. In a superinfection model, prior infection with pandemic H1N1 influenza virus (strain A/England/195/2009) augmented NTHi infection severity, even with a lower bacterial challenge dose. Immunization with PHiD-CV produced high levels of antibodies that were specific against Protein D, but not heat-killed NTHi. Immunization with PHiD-CV led to a slight reduction in bacterial load, but no change in disease outcome. Conclusions: PHiD-CV induced high levels of Protein D-specific antibodies, but did not augment pulmonary clearance of NTHi. We found no evidence to suggest that PHiD-CV will offer added benefit by preventing NTHi lung infection.